A REVIEW OF DSS (ESPECIALLY GDSS) SOFTWARE MARKET WITH A FOCUS ON DECISION MAKING FOR COMPLEX PRODUCTS AND PROCESSES - MIR, OWAIS (2012)
Global competition and complex business environment are forcing organizational managers to think out of the box and exploit every opportunity to involve everyone in complex decision making situations. These situations need typical software systems (Decision Support Systems and Group Decision Support Systems) to address the complex problems. This dissertation involves a critical review of DSS (especially GDSS) software market. Fourteen general softwares are selected and examined of features and their projected effects on group structures and effectiveness in decision making. The research also involves study of pilot cases from amePLM project. The problems identified in the case studies are then used to recognize the best software to each pilot company. Finally, a theoretical framework for an ultimate GDSS is proposed based on field studies and software studies. The research is based on qualitative data and actor perception of data is used. A detailed analysis of group decision softwares suggests that many of these softwares offer almost all GDSS features and also provides superior group interaction and communication. Although these softwares provide excellent support but there is always room for improvement. New technologies need to be explored and incorporated into GDSS to fulfil growing need of highly complex decisions.